2021
DOI: 10.3390/ma14030675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Particle Size and Matrix Strength on Strengthening and Damage Process of the Particle Reinforced Metal Matrix Composites

Abstract: Roles of the particle, strengthening, and weakening during deformation of the particle reinforced metal matrix composite, were studied using in situ technique. Composites with three different strengths Al-Cu-Mg alloy matrices reinforced by three sizes SiC particles were manufactured and subjected to in situ tensile testing. Based on in situ observation, damage process, fraction and size distribution of the cracked particles were collected to investigate the behavior of the particle during composite deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…60µm of epoxy/0%CSAC:100%PKSAC samples showed lesser ductility than 105 and 150 µm, which reveal that an increase in particle size increases ductility. This conforms to the conclusions of [7,19,23] that when the particle size increases, the elongation of the composite can either increase or decrease [6,7,24] in different strength matrices. It is essential to achieve a relatively high ductility when pursuing a higher-strength composite [24].…”
Section: Mechanical Properties Of Fabricated Samplessupporting
confidence: 90%
“…60µm of epoxy/0%CSAC:100%PKSAC samples showed lesser ductility than 105 and 150 µm, which reveal that an increase in particle size increases ductility. This conforms to the conclusions of [7,19,23] that when the particle size increases, the elongation of the composite can either increase or decrease [6,7,24] in different strength matrices. It is essential to achieve a relatively high ductility when pursuing a higher-strength composite [24].…”
Section: Mechanical Properties Of Fabricated Samplessupporting
confidence: 90%
“…From previous studies, it was concluded that using of fillers with a small average particle size and narrow size range can obtain an improved strengthening effect on the composites [ 64 , 65 ]. Furthermore, it has been noted that a relatively small weight percentage of nano-sized particle can result in a significantly improved mechanical properties [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher loads accelerate abrasive wear due to increased local tension, resulting in deeper grooves. 62 The dislocation density is raised due to the work hardening effect resulting from thermal mismatch between the particle and the base material. With an increase in load, dislocations move through the particle's pileup dislocation at the grain boundary, while stress concentration induces delamination cracks at the particle or matrix material, caused by shear deformation at the subsurface.…”
Section: Physicomechanical Properties Testmentioning
confidence: 99%